2004
DOI: 10.1038/sj.cr.7290219
|View full text |Cite
|
Sign up to set email alerts
|

Induction of antiproliferative effect by diosgenin through activation of p53, release of apoptosis-inducing factor (AIF) and modulation of caspase-3 activity in different human cancer cells

Abstract: Previously, we demonstrated that a plant steroid, diosgenin, altered cell cycle distribution and induced apoptosis in the human osteosarcoma 1547 cell line. The objective of this study was to investigate if the antiproliferative effect of diosgenin was similar for different human cancer cell lines such as laryngocarcinoma HEp-2 and melanoma M4Beu cells. Moreover, this work essentially focused on the mitochondrial pathway. We found that diosgenin had an important and similar antiproliferative effect on differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
90
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(93 citation statements)
references
References 41 publications
3
90
0
Order By: Relevance
“…Mitochondria play an important role in apoptotic pathways resulted from a variety of events including the release of caspase activators, changes of the MMP, ROS generation, and regulation of Bcl-2 family proteins (Corbiere et al, 2004;Ekert et al, 1999). According to our data, significant loss of MMP was observed in cells co-treated with Wit A and IR (Fig.…”
Section: Discussionsupporting
confidence: 50%
“…Mitochondria play an important role in apoptotic pathways resulted from a variety of events including the release of caspase activators, changes of the MMP, ROS generation, and regulation of Bcl-2 family proteins (Corbiere et al, 2004;Ekert et al, 1999). According to our data, significant loss of MMP was observed in cells co-treated with Wit A and IR (Fig.…”
Section: Discussionsupporting
confidence: 50%
“…Finally downregulation of AIF expression by AIF-siRNA diminished A3D8-induced cell death suggesting that AIF is required for CD44-induced in HEL cells. Recent studies have suggested that AIF is a central mediator of relevant experimental models of cell death (Corbiere et al, 2004;Kang et al, 2004;Liu et al, 2004a;Cheung et al, 2005;Ishitsuka et al, 2005;Park et al, 2005). However, AIF is a janus protein with a vital role in cells via its redox activity, and a lethal role by participating to chromatinolysis and chromatin condensation once translocated to the nucleus (Lipton and Bossy-Wetzel, 2002;Vahsen et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…PARP-1 is a member of the PARP family, which initiates DNA damage repair via the modification of poly adenosine diphosphate glycosylation receptor protein. PARP-1 has been shown to trigger apoptosis signaling and activate caspase-3 to induce cell apoptosis and DNA damage (24,29). Thus, we hypothesize that treatment with xanthohumol promoted PARP protein expression in laryngeal squamous cell carcinoma SCC4 cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that caspases are activated during tumor cell apoptosis (23). A series of novel caspase-related apoptosis-inducing pathways have been identified that may be targeted to control cancer, which have practical significance for the majority of tumors and thus, may result in breakthroughs with regard to the treatment of malignant tumors (24). The activation of caspase-9 and caspase-3 may underlie the apoptosis of fibroblasts in keloids (25).…”
Section: Discussionmentioning
confidence: 99%